1997
DOI: 10.1126/science.275.5299.530
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Serotonin Distribution in Live Cells with Three-Photon Excitation

Abstract: Tryptophan and serotonin were imaged with infrared illumination by three-photon excitation (3PE) of their native ultraviolet (UV) fluorescence. This technique, established by 3PE cross section measurements of tryptophan and the monoamines serotonin and dopamine, circumvents the limitations imposed by photodamage, scattering, and indiscriminate background encountered in other UV microscopies. Three-dimensionally resolved images are presented along with measurements of the serotonin concentration ( approximately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
303
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 410 publications
(305 citation statements)
references
References 19 publications
2
303
0
Order By: Relevance
“…While the nature of the water soluble component facilitating formation of the side reaction ergosterol D isomer was not identified, it has been reported that small amounts of nitric acid or mercuric nitrate catalyze the formation of the tetraene DHE as well as a side product, i.e., mercurated triene, and so such impurities may be possible contaminants in the original ergosterol (64). Recently, real-time multiphoton imaging of the naturally-occurring fluorescent sterol DHE in the plasma membrane of living cells (70,82,203,204) was used to examine sterol distribution directly with high optical sectioning capability (206)(207)(208)(209). While subcellular distribution (plasma membrane, lysosome, lipid droplet, etc) of DHE was highly dependent on the method of delivery (microcrystals, LUV, MβCD), DHE at the plasma membrane was found to be distributed non-randomly into sterol-rich and sterol-poor regions in plasma membranes of living cells with the size range of sterol-rich clustering domains estimated to be from 200 nm (limit of optical microscopy) to 565 nm (70,71,82,203).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…While the nature of the water soluble component facilitating formation of the side reaction ergosterol D isomer was not identified, it has been reported that small amounts of nitric acid or mercuric nitrate catalyze the formation of the tetraene DHE as well as a side product, i.e., mercurated triene, and so such impurities may be possible contaminants in the original ergosterol (64). Recently, real-time multiphoton imaging of the naturally-occurring fluorescent sterol DHE in the plasma membrane of living cells (70,82,203,204) was used to examine sterol distribution directly with high optical sectioning capability (206)(207)(208)(209). While subcellular distribution (plasma membrane, lysosome, lipid droplet, etc) of DHE was highly dependent on the method of delivery (microcrystals, LUV, MβCD), DHE at the plasma membrane was found to be distributed non-randomly into sterol-rich and sterol-poor regions in plasma membranes of living cells with the size range of sterol-rich clustering domains estimated to be from 200 nm (limit of optical microscopy) to 565 nm (70,71,82,203).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Based on this technique, visualization of the intracellular mitochondria (Barzda et al, 2005) and quantification of intracellular serotonin (Maiti et al, 1997) and NAD(P)H (Patterson et al, 2000) have been reported. It makes high-resolution imaging of endogenous fluorophores possible and is well suited to intrinsic molecular imaging in biological specimens.…”
Section: Corneal 2-photon Excitation Imagingmentioning
confidence: 99%
“…Fourth, an isoelectric focusing gel of the unlabeled lysozyme showed only one band, indicating that the lysozyme preparation was very pure in terms of the charge of its constituent proteins, reducing the likelihood that impurities or lysozyme isoforms are the source of the observed overshoot. Finally, to eliminate fluorescent probes completely, we conducted experiments using multiphoton excitation to obtain uptake images from the intrinsic fluorescence of the tryptophan residues in lysozyme (19). Excitation was with a mode-locked titanium:sapphire laser (Coherent Radiation, Palo Alto, CA) with ϭ 718 nm and a pulse frequency of Ϸ80 MHz.…”
Section: Figmentioning
confidence: 99%